Analisis implementasi sistem pengendalian intern pemerintahan (SPIP), disiplin kerja dan lingkungan kerja terhadap kinerja pegawai: Studi pada Dinas Perhubungan Provinsi Lampung - Salma, Isyfa Yulia; Devi, Yulistia (Journal of Accounting and Digital Finance, 2024)
This study examines the influence of the government’s internal control system, work discipline, and work environment on employee performance at the Lampung Provincial Transportation Office. This type of research is tentative primary data. The population of all employees at the Lampung Provincial Transportation Office and 60 samples used the purposive sampling method. The data collection method used was a Likert scale questionnaire. The data analysis method is multiple regression analysis. This study’s findings were that the government’s internal control system and the work environment had a significant effect on employee performance, and work discipline had no effect on employee performance. While employee performance from an Islamic perspective, Islam views work as part of worship and jihad if work is consistent with Allah’s regulations and must be accompanied by good work management as well.